2023
DOI: 10.4018/978-1-6684-7494-5.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization and Crises

Abstract: The aftermath of globalization resulted in people coming to be global citizens. Though, the technology advancement and its adoption in organizations creating and allowing both customers and employees savoring new experiences. Furthermore, technology helps airlines facilitate the task, elevate performance, and accommodate customer's comfort. And yet, the training and development is required for the improvement of human resource competencies. The aims of this study were to: (1) investigate human resource develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…HRD would change the attitude and behavior and elevate competence and performance (Kankaew et al, 2023). Then, HRD is flourishing with the abilities, expertise, and competence of the workforce.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…HRD would change the attitude and behavior and elevate competence and performance (Kankaew et al, 2023). Then, HRD is flourishing with the abilities, expertise, and competence of the workforce.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several types of training and development have been imposed by scholars, as Kankaew et al (2023) indicated, including classroom, field trip, education, mentoring, job rotation, onthe-job training, and off-the-job training. Initially, the training is based on the principal concepts, the organization's requirements, and its behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The seamless integration of technology into various HRM processes has ushered in a new era of efficiency, data-driven decision-making, and enhanced employee experiences. From recruitment and training to performance management and employee engagement, technology has emerged as a powerful tool that shapes the way aviation companies manage their workforce (Kankaew et al, 2023). This section explores the intricate relationship between technological integration and HRM in the aviation sector, delving into the ways in which airlines harness technology to optimize HRM practices and ensure a competitive edge in an increasingly digital era.…”
Section: 5technological Integration and Hrmmentioning
confidence: 99%
“…Company A series of changes that have occurred, such as globalization, an increase in knowledge work, the acceleration of technological progress, and increased competition, make it important for institutions to have superior and competitive human resources for organizational success (Kankaew et al, 2023;Li, 2023). Employers must grasp newly discovered fields in the workplace and need certain competences from employees, including a combination of technical and non-technical skills (Ternikov, 2022).…”
Section: Introductionmentioning
confidence: 99%